Understanding early-stage radiation damage in nuclear alloys through positron annihilation and semi-empirical modeling - Vladimír Kršjak; Yamin Song; Veronika Lučanská; Stanislav Sojak; Pavol Noga; Martin Petriska; Branislav Stríbrnský; Sofia Gašparová; Igor Neuhold; Matej Kubiš; Dušan Vaňa; Tielong Shen; et al. (npj Materials Degradation)
Abstract The recognition of the early stage of radiation aging and the aggregation of point defects into nanometric clusters pose significant challenges for nuclear structural materials. In this study, we employ positron annihilation spectroscopy to characterize various alloys exposed to severe radiation conditions. A novel approach to data evaluation enables a detailed description of helium-vacancy interactions in defects, ranging from small vacancy clusters to nanometric helium bubbles. This study combines two irradiation experiments to clarify the role of ballistic damage, helium production rates, and irradiation temperature. The obtained data serve as the foundation for a new semi-empirical model that elucidates positron trapping at helium-vacancy clusters and provides realistic experimental equilibrium helium-to-vacancy ratios across a wide range of defect sizes. This work complements and expands current understanding of helium bubble swelling in nuclear materials, offering new insights into the microstructural evolution of materials for the next generation of nuclear facilities.